Selective electrochemical production of hydrogen peroxide at zigzag edges of exfoliated molybdenum telluride nanoflakes - Coleman, Jonathan (My University, 2020)
The two-electron reduction of molecular oxygen represents an effective strategy to enable the green, mild and on-demand synthesis of hydrogen peroxide. Its practical viability, however, hinges on the development of advanced electrocatalysts, preferably composed of non-precious elements, to selectively expedite this reaction, particularly in acidic medium. Our study here introduces 2H-MoTe2 for the first time as the efficient non-precious-metal-based electrocatalyst for the electrochemical production of hydrogen peroxide in acids. We show that exfoliated 2H-MoTe2 nanoflakes have high activity (onset overpotential ∼140 mV and large mass activity of 27 A g−1 at 0.4 V versus reversible hydrogen electrode), great selectivity (H2O2 percentage up to 93%) and decent stability in 0.5 M H2SO4. Theoretical simulations evidence that the high activity and selectivity of 2H-MoTe2 arise from the proper binding energies of HOO* and O* at its zigzag edges that jointly favor the two-electron reduction instead of the four-electron reduction of molecular oxygen.
Keywords: electrocatalyst; synthesis of hydrogen peroxide; exfoliated 2H-MoTe2 nanoflakes; Hydrogen peroxide production; Non-precious-metal-based electrocatalyst; Molybdenumtelluride; Liquid-phase exfoliation; Zigzag edges